Normal monthly and annual precipitation for Eastern Colorado - Schulz, Edmund F., author; Smith, George L., author; Colorado State University, publisher (Colorado State University. Libraries, 1962)
Isohyetal maps are given for each month of the year as well as the expected annual precipitation. The maps are for that portion of Colorado lying east of the region defined physiographically as the Rocky Mountain Foothills. They were prepared by means of the double-mass-curve technique, which identifies trends in precipitation data due to changes in station location or observing techniques. The data examined was for the period January 1, 1941 to December 31, 1961. The stations used in data analysis were grouped on both a geographic and physiographic basis.
CER62GLS48.
July 1962.
Keywords: Precipitation (Meteorology) -- Colorado